CITRA POSITIF LAKI-LAKI BATAK DALAM FILM NGERI-NGERI SEDAP (Analisis Semiotika Roland Barthes) - Sagala, Ronal Arpandi; Hasan, Kamaruddin (Jurnal Jurnalisme, 2024)
In the mass media industry, films can perpetuate stereotypes about certain ethnic groups. For example, the Batak tribe is often described as a tough and strict tribe, especially towards men. The film 'Ngeri-Ngeri Sedap' released in 2022 is the latest example of this, depicting family conflict in a Batak family. This research analyzes the film 'Ngeri-Ngeri Sedap' using Roland Barthes' semiotic analysis, focusing on aspects of Denotation, Connotation and Myth. Other important values are Hamoraon (wealth), Hagabeon (offspring), and Hasangapon (honor). The film "Ngeri-Ngeri Sedap" depicts these characteristics through its characters, showing how the Batak cultural values instilled by parents make Batak boys appear tough. The aim of this research is to provide a deeper understanding of the image of men. Batak men depicted in the film. This film analysis includes every scene and shot, as well as related articles about the customs and culture of the Batak tribe. This analysis aims to reveal how stereotypes of the Batak tribe are depicted in films and how this depiction impacts the audience's perception of their ethnic identity